Libraries and Colonial Contexts: A Conversation with Researchers from the Global South - Gouaffo, Albert; Hillebrecht, Werner; Kamardeen , Naazima; Kyany’a, Mutanu; Müller, Lars (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2024)
Librarians and academics from German-speaking countries met at the workshop "Colonial Contexts in Libraries "(Koloniale Kontexte in Bibliotheken) at the Staatsbibliothek zu Berlin on 6 and 7 November 2023. The objective of the event was to discuss colonial entanglements of collections and to open up perspectives for a contemporary and responsible approach to colonial heritage in libraries. In addition, international experts were invited to contribute video statements on new perspectives and give impulses to the debate. For this issue of o-bib, these statements were converted into a virtual interview in order to share them with a wider audience.
Keywords: Colonial contexts; Digitization; Global South; Restitution; Collaboration